GOIGS AND GOZOS (THIRTEENTH - SIXTEEENTH CENTURIES) HISTORICAL, METRICAL, MUSICAL NOTES, AND RESEARCH INSIGHTS. - MELE, GIAMPAOLO (Imago Temporis. Medium Aevum, 2023)
The flourishing literary and musical production of goigs (in Catalan), gozos (in Castilian), and gosos/gòccius (in Sardinian), is a rare case of a poetic - musical phenomenon of Romance origin --with a strophic structure peculiar to the diverse typologies of fornies fixes- that is still alive today, both in the written and oral tradition. The purpose of this note is to provide a preliminary, diachronic overview of the sources and main studies on both goigs and gozos, from their origins down to the first half of the 16 century. The review will be complemented by historical, metrical and musical observations, from an interdisciplinary perspective, and with hints for research and/or further study.